Numerical analysis of non-Newtonian nanofluids under double-diffusive regimes - Sher Akbar, Noreen; Mallawi, Fouad Othman (Frontiers in Materials, 2023)
In the present study, the slip velocity of a non-Newtonian fluid flowing above a continuously stretching surface with double-diffusive nanofluid is examined at prespecified values of surface temperature, while also accounting for salt concentration. An initial set of partial differential equations, along with the boundary conditions, are first cast into a dimensionless form; subsequently, the comparation variables are invoked to reduce the partial differential equations to ordinary differential equations; and finally, the reduced ordinary differential equations are solved numerically via the shooting method. Values for dimensionless velocity, temperature, salt concentration distribution, local Nusselt number, and Sherwood number are calculated numerically and presented visually in a set of graphs. A extensive parametric study is conducted to probe the effects of adjusting various parameters in the cases of both assisting and opposing flow.